PENGARUH SENI KALIGRAFI DALAM MENUMBUHKAN KEMANDIRIAN FINANSIAL BAGI MAHASISWA - Rabiatun Adawiyah (Jurnal Ekshis, 2024)
The art of calligraphy plays a significant role in fostering financial independence among students. Through intensive practice and meticulous attention to detail, this art form strengthens skills such as precision, patience, and creativity, crucial for personal financial management. This article explores how calligraphy can serve as an effective educational tool to enhance students' understanding of the importance of discipline, planning, and financial stewardship. Implementing calligraphy practices within higher education enriches visual culture and positively influences students' attitudes toward financial autonomy and responsibility. The method used in this research is qualitative, where the researcher collected data through online interviews and observations with informants. Additionally, the researcher referenced various theories from literature reviews such as scientific journals, books, and reliable information. The research findings indicate that the marketing strategy employed towards the informants involved online marketing strategies, including platforms like Facebook, Instagram, and WhatsApp. Through these strategies, they experienced increased sales. Furthermore, the informants implemented changes in product quality and sales services to ensure customer comfort and loyalty.